Integrative Metabolomic and Transcriptomic Analyses Uncover Metabolic Alterations and Pigment Diversity in Monascus in Response to Different Nitrogen Sources - Di Huang (American Society for Microbiology, 2021)

(untitled)
Natural MPs containing a mixture of red, orange, and yellow pigments are widely used as food coloring agents. MP diversity provides foods with versatile colors and health benefits but, in turn, complicate efforts to achieve maximum yield or desirable combination of pigments during the manufacturing process.